A Shared Perspective for PGIS and VGI. (1st October 2016) - Verplanke, Jeroen; McCall, Michael K.; Uberhuaga, Claudia; Rambaldi, Giacomo; Haklay, Muki
Abstract : This paper reviews persistent principles of participation processes. On the basis of a review of recent interrogations of the (Public) Participatory Geographic Information Systems (P)PGIS and Volunteered Geographic Information (VGI) approaches, a summary of five prevailing principles in participatory spatial information handling is presented. We investigate these five principles that are common to (P)PGIS and VGI on the basis of a framework of two dimensions that govern the participatory use of spatial information from the perspective of people and society. This framework is presented as a shared perspective of (P)PGIS and VGI and illustrates that, although both share many of these same principles, the ways in which these principles are approached are highly diverse. The paper ends with a future outlook in which we discuss the inter-connected memes of potential technological futures, the signification of localness in 'local spatial knowledge', and the ramifications of ethical tenets by which PGIS and VGI can strengthen each other as two sides of the same coin.